2021
DOI: 10.1089/omi.2021.0049
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Multipotent Human Mesenchymal Stem/Stromal Cells: Learning from History and Advancing Clinical Applications

Abstract: Early reports demonstrated the presence of cells with stem-like properties in bone marrow, with these cells having both hematopoietic and mesenchymal lineages. Over the years, various investigations have purified and characterized mesenchymal stromal/stem cells (MSCs) from different human tissues as cells with multi-lineage differentiation potential under the appropriate conditions. Due to their appealing characteristics and potential, MSCs are leveraged in many applications including medicine, oncology, biopr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 228 publications
(273 reference statements)
0
14
0
1
Order By: Relevance
“…The development of new and advanced therapeutic alternatives for bone healing and regeneration such as orthobiologics application is conveying optimism among orthopedic surgeons and researchers, as evidenced by the numerous studies and systematic reviews found in the literature ( Alonso-Goulart et al, 2021 ; Zhang S et al, 2021 ; Dzobo, 2021 ; Fu et al, 2021 ; Wilson et al, 2021 ). Although several autologous BMA-based products, such as BMC and whole BMA, have been widely proposed for bone regeneration, the distinctive and enhanced biological and physical properties of clotted BMA make it an excellent candidate for autologous cell therapy ( Veronesi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of new and advanced therapeutic alternatives for bone healing and regeneration such as orthobiologics application is conveying optimism among orthopedic surgeons and researchers, as evidenced by the numerous studies and systematic reviews found in the literature ( Alonso-Goulart et al, 2021 ; Zhang S et al, 2021 ; Dzobo, 2021 ; Fu et al, 2021 ; Wilson et al, 2021 ). Although several autologous BMA-based products, such as BMC and whole BMA, have been widely proposed for bone regeneration, the distinctive and enhanced biological and physical properties of clotted BMA make it an excellent candidate for autologous cell therapy ( Veronesi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a scaffold should account for the specific needs of each cell type in the periodontium and allow for cellular adhesion, spreading, and proliferation. Its biomechanical properties, i.e., the spacing of cell adhesion points and the stiffness/elastic modulus (Young's modulus), should be permissive for supporting and maintaining the proper differentiation of the cells of interest [58][59][60][61][62][63][64]. In previous studies, we showed that a gelatin/polycaprolactonebased nonwoven was suitable for establishing cocultures of GKs and GFs [31], proper stratification of keratinocytes [30,32], and substantial in vivo periodontal tissue engineering in a minipig soft tissue dehiscence model [31].…”
Section: Introductionmentioning
confidence: 99%
“…hMSCs have gained increasing attention in the field of biomedicine over the last three decades [7,[62][63][64]. Because of their developmental potency, hMSCs can differentiate into various cell types, including fibroblasts, adipocytes, chondrocytes, and osteoblasts [65,66].…”
Section: Introductionmentioning
confidence: 99%
“…MSC have interesting immunomodulatory and regenerative properties. Therefore, such cells and their secretome have promising potential for applications in regenerative medicine [14,16]. At the research level, MSC are also widely used as an in vitro model for the study of cell differentiation.…”
Section: Introductionmentioning
confidence: 99%